Association between neurological soft signs, temperament and character in patients with schizophrenia and non-psychotic relatives - Galindo, Liliana; Pastoriza, Francisco; Bergé, Daniel; Mané, Anna; Picado, Marisol; Bulbena, Antonio; Robledo, Patricia; Pérez, Victor; Vilarroya, Oscar; Cloninger, Claude Robert (PeerJ, 2016)
The heritability of schizophrenia and most personality traits has been well established, but the role of personality in susceptibility to schizophrenia remains uncertain. The aim of this study was to test for an association between personality traits and Neurological Soft Signs (NSS), a well-known biological marker of schizophrenia, in non-psychotic relatives of patients with schizophrenia. For this purpose, we evaluated the NSS scale and personality measured by the Temperament and Character inventory (TCI-R) in three groups of subjects: 29 patients with schizophrenia, 24 unaffected relatives and 37 controls. The results showed that patients with schizophrenia were more asocial (higher harm avoidance and lower reward dependence), more perseverative (higher persistence), and more schizotypal (lower self-directedness and cooperativeness, higher self-transcendence). The unaffected relatives showed higher harm avoidance, lower self-directedness and cooperativeness than the healthy controls. Higher NSS scores and sub-scores were found in patients and non-psychotic relatives compared with the controls. Among all the patients, total NSS scores were positively correlated with harm avoidance but negatively correlated with novelty seeking and persistence. Total NSS were also correlated with low scores on self-directedness and cooperativeness, which are indicators of personality disorder. Our results show that susceptibility to NSS and to schizophrenia are both related to individual differences in the temperament and character features in non-psychotic relatives of patients with schizophrenia. High harm avoidance, low persistence, low self-directedness and low cooperativeness contribute to both the risk of NSS and schizophrenia. These findings highlight the value of using both assessments to study high risk populations.
Keywords: Schizophrenia; Neurological Soft Signs; Temperament and character; Vulnerability markers; Personality